Simulation model of 1-phase pulse-width modulation rectifier by using MATLAB/Simulink - Salam Waley Shneen; Ghada Adel Aziz; Fatin Nabeel Abdullah; Dina Harith Shaker (Institute of Advanced Engineering and Science, 2022)
One of the problems that need to be solved is the difference in the type of nutrition from the load. The feeding may be from a constant current source such as batteries and solar cells, and there are alternating current sources such as diesel machines, wind energy, and various power plants. All of these sources need electronic power devices that help convert and regulate the control and control of the type of feeding on the one hand and its amount on the other. From here, we show the size of the challenge occupied by electronic power transformers, as they are considered the solution to many problems of transmission, distribution, and feeding systems for different loads. The current study sheds light on one of the types of electronic power systems, which is unified. Choosing and suggesting a set of single-phase unifying circuits to conduct simulations and come up with results that are analyzed to show the function of the non-electronic modulators. In the current simulation, tests were carried out for a group of circuits that need direct current (DC) power, and their available source of supply is an alternating current source to different departments to access a set of data that enables researchers to conduct appropriate analyzes to perform them, by discussing those results.